2018
DOI: 10.1016/j.ebiom.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Typhi Colonization Provokes Extensive Transcriptional Changes Aimed at Evading Host Mucosal Immune Defense During Early Infection of Human Intestinal Tissue

Abstract: Commensal microorganisms influence a variety of host functions in the gut, including immune response, glucose homeostasis, metabolic pathways and oxidative stress, among others. This study describes how Salmonella Typhi, the pathogen responsible for typhoid fever, uses similar strategies to escape immune defense responses and survive within its human host. To elucidate the early mechanisms of typhoid fever, we performed studies using healthy human intestinal tissue samples and “mini-guts,” organoids grown from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 79 publications
5
74
0
Order By: Relevance
“…Using enteroids with reversed polarity, the authors showed that S. Typhimurium invades and induces actin ruffles more efficiently at the apical surface compared to the basolateral surface. The authors observed a more diffuse process of epithelial invasion rather than invasion only or predominantly at the M cells [144], which confirmed the S. Typhi observations by Nickerson, KP et al [71].…”
Section: Human-derived Modelssupporting
confidence: 83%
See 2 more Smart Citations
“…Using enteroids with reversed polarity, the authors showed that S. Typhimurium invades and induces actin ruffles more efficiently at the apical surface compared to the basolateral surface. The authors observed a more diffuse process of epithelial invasion rather than invasion only or predominantly at the M cells [144], which confirmed the S. Typhi observations by Nickerson, KP et al [71].…”
Section: Human-derived Modelssupporting
confidence: 83%
“…The fidelity of organoid-derived data in representing human disease was further demonstrated in 2018 by Nickerson, KP and colleagues [71], who compared infection of human tissue biopsies and human intestinal enteroid-derived monolayers seeded on a 2D Transwell system, and observed that the enteroid-derived epithelial monolayers recapitulated S. Typhi infection observations made in the tissue biopsy model. The authors also carried out transcriptional profiling of both the host tissue and the bacteria in order to determine early critical interactions.…”
Section: Human-derived Modelsmentioning
confidence: 91%
See 1 more Smart Citation
“…Cases of the disease among African children decrease, and increase in the acquisition of the antibody to start all complement-dependent killing of Salmonella, and subsequently, more effective blood phagocytes and opsoniza-tion (4)(5)(6). Measuring and detecting serum antibody markers in the clinical laboratory to evaluate a patient's health status is an important and valuable issue (6)(7)(8)(9)(10)(11). The affinity of an antibody to its antigen describes and characterizes the strength of the interaction between the antibody and the antigen and plays a critical role in the recovery of infection.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the early stages of S. Typhi infection have been investigated in intestinal biopsies and in organoids derived from human intestinal epithelial tissue (7). Infected biopsies were used to monitor transcriptional changes in the host and the pathogen, to determine cytokine profiling, and to perform electron microscopy observation.…”
mentioning
confidence: 99%